Hemophagocytic lymphohistiocytosis in COVID-19: Case reports of a stepwise approach. Issue 12 (26th March 2021) - Schnaubelt, Sebastian; Tihanyi, Daniel; Strassl, Robert; Schmidt, Ralf; Anders, Sonja; Laggner, Anton N.; Agis, Hermine; Domanovits, Hans
Abstract: Rationale: The immunologic syndrome induced by severe acute coronavirus disease 2019 (COVID-19) is yet not fully understood. Typical patterns of clinical and laboratory features match secondary hemophagocytic lymphohistiocytosis (sHLH). However, the optimal approach to COVID-19 patients testing positive for sHLH is still unclear. Patient concerns: Three patients with COVID-19 are reviewed. All showed hyperinflammation and cytokine storm, necessitating intensive care treatment including mechanical ventilation. Diagnosis: Secondary hemophagocytic lymphohistiocytosis due to severe COVID-19; diagnosed via HScore. Interventions: A treatment regimen of methylprednisolone, pentaglobin, and anakinra was developed and administered. Outcomes: One patient survived the ICU stay. Two other patients, in whom sHLH was diagnosed too late, deceased. Lessons: A routine screening of COVID-19 patients for secondary HLH by using the HScore is feasible; especially those patients deteriorating clinically with no sufficient response to shock management might be at particular high risk. A stepwise therapeutic approach comprising corticosteroids, immunoglobulins and anakinra, accompanied by immunoadsorption, may dampen cytokine storm effects, and potentially reduce mortality. Abstract : Supplemental Digital Content is available in the text